Novel CRTC1::MRTFB(MKL2) Gene Fusion Detected in Myxoid Mesenchymal Neoplasms With Myogenic Differentiation Involving Bone and Soft Tissues - Warmke, Laura M; Collier, Christopher D; Niziolek, Paul J; Davis, Jessica L; Zou, Ying S; Michal, Michael; Bell, Robert C; Policarpio-Nicolas, Maria Luisa C; Cheng, Yu-Wei; Duckworth, Lauren; Dermawan, Josephine K; Fritchie, Karen J; et al. (Modern pathology, 2024)
Appropriate classification of fusion-driven bone and soft tissue neoplasms continues to evolve, often relying on the careful integration of morphologic findings with immunohistochemical, molecular, and clinical data. Herein, we present 3 cases of a morphologically distinct myxoid mesenchymal neoplasm with myogenic differentiation and novel CRTC1::MRTFB (formerly MKL2) gene fusion. Three tumors occurred in 1 male and 2 female patients with a median age of 72 years (range: 28-78). Tumors involved the left iliac bone, the right thigh, and the left perianal region with a median size of 4.0 cm (4.0-7.6 cm). Although 1 tumor presented as an incidental finding, the other 2 tumors were noted, given their persistent growth. At the time of the last follow-up, 1 patient was alive with unresected disease at 6 months, 1 patient was alive without evidence of disease at 12 months after surgery, and 1 patient died of disease 24 months after diagnosis. On histologic sections, the tumors showed multinodular growth and were composed of variably cellular spindle to round-shaped cells with distinct brightly eosinophilic cytoplasm embedded within a myxoid stroma. One tumor showed overt smooth muscle differentiation. Cytologic atypia and mitotic activity ranged from minimal (2 cases) to high (1 case). By immunohistochemistry, the neoplastic cells expressed focal smooth muscle actin, h-caldesmon, and desmin in all tested cases. Skeletal muscle markers were negative. Next-generation sequencing detected nearly identical CRTC1::MRTFB gene fusions in all cases. We suggest that myxoid mesenchymal tumors with myogenic differentiation harboring a CRTC1::MRTFB fusion may represent a previously unrecognized, distinctive entity that involves soft tissue and bone. Continued identification of these novel myxoid neoplasms with myogenic differentiation will be important in determining appropriate classification, understanding biologic potential, and creating treatment paradigms.
Keywords: buněčná diferenciace; Gene Fusion; Soft Tissue Neoplasms; Humans; nádory kostí; Transcription Factors; vývoj svalů; Biomarkers, Tumor; fúzní onkogenní proteiny; Female; Aged; Bone Neoplasms; dospělí; senioři; lidé; CRTC1::MRTFB; myogenic; nádory měkkých tkání; Oncogene Proteins, Fusion; nádorové biomarkery; Adult; Trans-Activators; ženské pohlaví; Male; trans-aktivátory; Cell Differentiation; transkripční faktory; fúze genů; mužské pohlaví; myxoid mesenchymal tumor; Muscle Development